Avaliação do desempenho de diferentes tipos de nanotubos de carbono na determinação de íons metálicos e ácido mefenâmico - Zidoi, Luciana (Universidade Federal de São Carlos, 2008)
This work is summarized in the evaluation of the acting of different types of carbon nanotubes (CNTs) in the determination of metallic íons. The appraised electrodes differ amongst themselves for the form of synthesis of the carbon nanotubes, that they take the formation of different types of NTCs with varied diameters. The multi-walled carbon nanotubes (MWCNTs) present diameters of 20-40 nm and of 110-190 nm. The single walled carbon nanotubes (SWCNT) present a smaller diameter than 2 nm. Already the electrodes of aligned multi-walled carbon nanotubo (AMWCNT) possess a diameter of 10-20 nm. The used technique was the one of anodic stripping differential pulse for the determination of a quartet of metallic íons, very known in the literature: Zn (II), Cd (II), Pb (II) and Cu (II). The metals were determined simultaneously, in a solution of acetate buffer 0.1 mol L-1, pH 4.8, containing íons Hg2 2+ in solution for the formation of one amalgam in the surface of the electrode, facilitating with that the deposition metallic íons. The parameters used for this study were: time of deposition of 120 s, in a potential of -1.2 V, time of preequilibrium of 10 s, scan rate of 20 mV s-1, width of pulse of 50 mV and potential range from -1.3 to 0.1 V. Observed that so much the electrode of NTCPMs (20-40 nm) as the electrode of NTCPU (< 2nm), they were the ones that presented better values of detection limits, quantification limits and sensibility, for Cd (II), Pb (II) and Cu (II). Already the best results for the determination of the ion Zn (II) they are in the electrode of NTCPMs of larger diameters (110-190 nm). An brief study, it was also accomplished, for the determination of a biological composition in phosphate buffer, pH 7.1, the mefenamic acid, a medicine that presents activities anti-inflammatory, analgesic, and anti-thermal and they were obtained good results.
Keywords: Nanotubos de carbono; Íons metálicos; Ácido mefenâmico; CIENCIAS EXATAS E DA TERRA::QUIMICA